Protective sexual behaviours among young adults in Nigeria: influence of family support and living with both parents - Anthony Idowu Ajayi; Sylvester Reuben Okeke (BMC, 2019)
Abstract Background Many studies have focused on risky sexual behaviour among adolescents and young adults; however, literature on protective sexual practices among this age cohort is still evolving. Since young adults are disproportionately burdened by sexually transmissible infections, including HIV, understanding factors that influence protective sexual behaviour among the age group is crucial in developing age-appropriate interventions. Drawing from a cross-sectional survey conducted among adolescents and young adults in two Nigerian universities, we examined gender differences in protective sexual behaviours and the influence of family support and living with both parents on these behaviours. Methods A total of 800 male and female university students in two Nigerian universities were recruited using stratified random sampling between February and April 2018. Analysis was, however, based on 599 participants aged between 15 and 24 . Adjusted and unadjusted multinomial logistic regression models were used to examine the influence of family support, and living with both parents on protective sexual behaviours at a 95% confidence interval. Results Findings show that the largest proportion of our participants engaged in protective sexual behaviours. We found no gender differences in protective sexual behaviours, including sexual abstinence, consistent condom use, and sexual fidelity. Family support and living with both parents were positively associated with protective sexual behaviours among adolescents and young adults. Conclusion This study found that a majority of adolescents and young adults in Nigerian Universities engage in protective sexual behaviours. Adequate family support and living with both parents are positively associated with protective sexual behaviours. The study however revealed that about one-fifth of our participants engaged in high-risk sexual behaviour. This suggests a need for behavioural change interventions, provision of sexual health services and empowerment of students who receive inadequate family support.